Epstein-Barr Virus Immune Response in High-Risk Nasopharyngeal Carcinoma Families in Greenland - 劉玫英; 陳振陽; Friborg, Jeppe; Jarrett, Ruth F.; Liu, Mei-Ying; Falk, Kerstin I.; Koch, Anders; Olsen, Ove R.; Duncan, Pamela; Wohlfarht, Jan; Chen, Jen-Yang; Melbye, Mads (2007)
Undifferentiated nasopharyngeal carcinoma is associated with Epstein-Barr virus (EBV) infection. Presence of EBV IgA antibodies is rare among healthy individuals and is used as a marker of nasopharyngeal carcinoma in high-incidence populations. Reasons for EBV IgA seropositivity are unknown, but high EBV IgA levels have been found among unaffected close family members and spouses to nasopharyngeal carcinoma patients in Chinese populations. In Greenland, a nasopharyngeal carcinoma-high-incidence area , we compared EBV serology and viral load in high-risk nasopharyngeal carcinoma family members (N=20) and controls without nasopharyngeal carcinoma-affected relatives (N = 90). There was no significant difference in EBV viral loads between relatives and controls, and EBV was detected in plasma in 5. 0% of relatives and 11.4% of controls. There was no significant difference in EBV serology, but the seroprevalence of EBV viral capsid antigen (VCA) IgA was high in both relatives (25.0%) and controls (20.5%). Compared with anti-VCA IgA-negative, anti-VCA IgA- positive individuals had significantly higher EBV viral loads in peripheral blood mononuclear cells (PBMCs) (P<0.01). The very high prevalence of anti-VCA IgA indicates that this antibody is unsuitable for nasopharyngeal carcinoma screening among Inuits. 微生物學科暨研究所 醫學院 期刊論文